CdgC, a Cyclic-di-GMP Diguanylate Cyclase of Azospirillum baldaniorum Is Involved in Internalization to Wheat Roots - Sierra Cacho, Daniel; Zamorano Sánchez, David S.; Xiqui-Vázquez, Maria Luisa; Viruega Góngora, Víctor Iván; Ramírez-Mata, Alberto; Baca, Beatriz E. (Frontiers in Plant Science, 2021)
Azospirillum baldaniorum is a plant growth-promoting rhizobacterium (PGPR) capable of fixing nitrogen, the synthesis of several phytohormones including indole-acetic acid, and induction of plant defenses against phytopathogens. To establish a successful and prolonged bacteria-plant interaction, A. baldaniorum can form biofilms, bacterial communities embedded in a self-made matrix formed by extracellular polymeric substances which provide favorable conditions for survival. A key modulator of biofilm formation is the second messenger bis-(3'-5')-cyclic-dimeric-GMP (c-di-GMP), which is synthesized by diguanylate cyclases (DGC) and degraded by specific phosphodiesterases. In this study, we analyzed the contribution of a previously uncharacterized diguanylate cyclase designated CdgC, to biofilm formation and bacterial-plant interaction dynamics. We showed that CdgC is capable of altering c-di-GMP levels in a heterologous host, strongly supporting its function as a DGC. The deletion of cdgC resulted in alterations in the three-dimensional structure of biofilms in a nitrogen-source dependent manner. CdgC was required for optimal colonization of wheat roots. Since we also observed that CdgC played an important role in exopolysaccharide production, we propose that this signaling protein activates a physiological response that results in the strong attachment of bacteria to the roots, ultimately contributing to an optimal bacterium-plant interaction. Our results demonstrate that the ubiquitous second messenger c-di-GMP is a key factor in promoting plant colonization by the PGPR A. baldaniorum by allowing proficient internalization in wheat roots. Understanding the molecular basis of PGPR-plant interactions will enable the design of better biotechnological strategies of agro-industrial interest.